2023
DOI: 10.3390/metabo13070845
|View full text |Cite
|
Sign up to set email alerts
|

Made in the Womb: Maternal Programming of Offspring Cardiovascular Function by an Obesogenic Womb

Abstract: Obesity incidence has been increasing at an alarming rate, especially in women of reproductive age. It is estimated that 50% of pregnancies occur in overweight or obese women. It has been described that maternal obesity (MO) predisposes the offspring to an increased risk of developing many chronic diseases in an early stage of life, including obesity, type 2 diabetes, and cardiovascular disease (CVD). CVD is the main cause of death worldwide among men and women, and it is manifested in a sex-divergent way. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 225 publications
0
4
0
Order By: Relevance
“…While mitochondrial dysfunction is considered a key factor in the pathogenesis of metabolic diseases (Saris and Heymsfield, 2007;Sergi et al, 2019), mitochondria are also essential in intergenerational programming and the transmission of environmental effects to the next generations (Alhassen et al, 2021). Maternal obesity is directly linked with mitochondrial alterations, leading to placental dysfunction, modulating fetal growth and development (Sobrevia et al, 2020;Diniz et al, 2023), with gestational obesity directly affecting the offspring muscle metabolism (Walter and Klaus, 2014;Ampong et al, 2022). Previous research in inbred C57BL/6 mice suggested that ultrastructural aberrations in oocyte mitochondria induced by a maternal OB diet are transferred to the subsequent embryos.…”
Section: Introductionmentioning
confidence: 99%
“…While mitochondrial dysfunction is considered a key factor in the pathogenesis of metabolic diseases (Saris and Heymsfield, 2007;Sergi et al, 2019), mitochondria are also essential in intergenerational programming and the transmission of environmental effects to the next generations (Alhassen et al, 2021). Maternal obesity is directly linked with mitochondrial alterations, leading to placental dysfunction, modulating fetal growth and development (Sobrevia et al, 2020;Diniz et al, 2023), with gestational obesity directly affecting the offspring muscle metabolism (Walter and Klaus, 2014;Ampong et al, 2022). Previous research in inbred C57BL/6 mice suggested that ultrastructural aberrations in oocyte mitochondria induced by a maternal OB diet are transferred to the subsequent embryos.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unmanageable risk factors can also contribute to CD development, such as age, sex, and genetic background [3]. On top of that, recent research has suggested that the intrauterine environment, which is modulated by maternal behaviors and disease, including gestational diabetes mellitus (GDM) [4,5], maternal obesity (MO) [5][6][7][8], and IUGR [9], severely influences the offspring's CD development risk.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MO itself represents a highly prevalent pregnancy complication [5]. It is estimated that approximately 50% of pregnancies occur in overweight or obese women [6]. Both GDM and MO contribute to an increased risk of inducing a fetoplacental environment resembling prolonged hypoxia, along with other factors, such as maternal smoking, vascular dysfunction, and maternal nutrient reduction [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well accepted that maternal nutrition influences the intrauterine environment and, consequently, the offspring's short-and long-term health [4,5]. Maternal nutrient restriction is a common cause of intrauterine growth restriction (IUGR) [6], in which the fetus might not reach its full growth potential [7].…”
Section: Introductionmentioning
confidence: 99%